DESENVOLVIMENTO COMUNITÁRIO POR MEIO DA PRÁTICA DO TURISMO ÉTNICO: EXPERIÊNCIAS EM COLÔNIA WITMARSUM, PALMEIRA/PR - Holm, Carla Caroline (2015)
Community development can be understood as the process that seeks transformation of economic, social and environmental orders given locality, in order to reach all individuals with positive actions. Tourism can be seen as an activity that contributes in this process because it requires in its genesis the involvement of a multiple group of people in order to develop and, thus, turns locations with potential visitors attraction destinations. Thus, the objective of this research was to seek to know how ethnic tourism can assist in community development process Colônia Witmarsum, Palmeira/PR. The community is located in the city of Palmeira/PR and is located around 60 Km from the capital Curitiba. Colônia presents differential elements because it was formed from the (re) Immigration German Mennonites from the north of Europe; Mennonite be in this case is to be part of a socio-religious group that was formed in the 1500s during the Protestant Reformation, which sought the spread of church and state so that there was a more just and egalitarian society. The Mennonite name is given in honor of the leader of the group, Menno Simons, who along other gave rise to different religions, such as Lutherans and Calvinists, only to exemplify. With the formation of community in this locality in 1951 was also mounted an agricultural cooperative that supports the local economy, however, in 2000 became part of the economic environment to tourism and the presence of this activity serves as an alternative for residents with respect the generation of employment and income. From a qualitative research, whose method was a field of study, one can achieve the goal originally proposed and the scope of such literature were conducted in primary and secondary sources; site visits; and interviews that after compose the research material were analyzed from a survey by similarity of answers.. In this sense, it was identified that Colônia Witmarsum presents elements of the tangible and intangible heritage that can be better exploited by tourist activity and thus may contribute to: the generation of jobs; increasing family income; diversification of the local economy; appreciation of the local workforce, recovery and maintenance of the Mennonite German culture; minimizing the rural exodus; and improved quality of life of community members. It is by this that the place of study can develop taking into account the principles advocated for community development, since the presence of tourism focusing on ethnic and religious elements, there will be economic, social and environmental mobilizations, whose positive effects may be felt by all residents. Betting on ethnic tourism planning in the community is still a challenge for local entrepreneurs, given the multiple possibilities of segments that can be developed on site, however, the community features a variety of elements that make up its history and that can be used by tourism to ensure an activity that addresses various aspects of their own. Thus, here we present some reflections on the exploitation of this difference that can make Colônia Witmarsum a major destination in offering a differentiated tourist experience in the area you are in.